Indocyanine Green Fluorescence Imaging for Intraoperative Confirmation of Bile Flow from Hilar Microbile Ducts during Kasai Portoenterostomy - Muhammed Jaseel; Anu K. Vasudevan; Abhinav Sihag; Naresh Shanmugam; Srinivas Sankaranarayanan; Mohamed Rela; Priya Ramachandran (Journal of Indian Association of Pediatric Surgeons)
Aim: We studied the usefulness of indocyanine green (ICG) fluorescence imaging in identifying bile flow from hilar microbile ducts during Kasai portoenterostomy (KPE). Materials and Methods: We reviewed the records of all the children who underwent KPE over 10 months and reviewed the operation notes of those who received ICG. ICG (0.1 mg/kg) was injected into a peripheral vein 12 h before the incision. We noted the surgeon’s observation on bile flow after hilar dissection using ICG camera (KARL STORZ). The outcome of KPE (jaundice clearance with direct bilirubin of <2 mg/dL) was correlated with the bile flow identified by the surgeon and results were computed. Results: Fifteen children underwent KPE during this period, out of which 11 children received ICG. After dissection of the hilar plate, good bile drainage was observed from the right and left corners of the portal plate in seven children. Six of these children with good bile flow have been observed to be clearing jaundice. One child despite having good bile flow did not clear jaundice. All four children who had poor bile flow failed to clear jaundice. In children who had received ICG, we were able to predict jaundice clearance with an accuracy of 91% (10 out of 11 children). Conclusion: ICG can be used effectively to identify bile flow during KPE and good bile flow observed during surgery correlates with jaundice clearance.